PENGEMBANGAN LKPD BERBASIS PMRI UNTUK MATERI SUDUT PADA PEMBELAJARAN MATEMATIKA KELAS V SDN 37 LUBUKLINGGAU - Pupalingga, Septi Nursyafa'atin; Akmal Rijal; Novianti Mandasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The PMRI-Based Student Worksheet (LKPD) is a teaching material that is systematically designed to assist students in the learning process. This study aimed to develop a product in the form of a PMRI-Based Student Worksheet (LKPD) for Mathematics learning in Grade V at SD Negeri 37 Lubuklinggau and to produce a worksheet that is valid, practical, and effective. This study employed a Research and Development (R&D) method using the ADDIE development model. The research subjects were 22 fifth-grade students. Based on the validity analysis using Aiken’s V, the PMRI-based LKPD obtained a score of 0.84 from the language validator, 0.88 from the media validator, and 1.00 from the material validator. The practicality analysis based on teacher and student response questionnaires showed that the PMRI-based LKPD met the criteria of being very practical, with an average score of 92%. Furthermore, the effectiveness analysis resulted in an average N-Gain score of 0.71, which falls into the high category. Therefore, it can be concluded that the PMRI-based LKPD for Mathematics learning meets the criteria of validity, practicality, and effectiveness, making it suitable for use in the learning process.